Epistimologi Pendidikan Islam Persepektif Naquib Al-Attas - Muhamad Hanif Alatas (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
The hegemony of Western knowledge, which has penetrated the whole world, has also unknowingly penetrated the majority of Muslims. They accept it without deep reflection on the epistemology on which modern science is based. The view that modern science is the sole authority of science is slowly eroding the Islamic view of science. This study uses a literature study approach as the main methodology. Specific characteristics that form the basis for the development of knowledge in this study include a focus on data or text presented in the literature, without involving field data or direct observation through eye witnesses. The epistemology of monotheism described by Naquib describes a scientific approach that integrates elements from sensory experience, the spiritual dimension, intellectual capacity, and intuitive insight as a whole, with the aim of gaining knowledge. It also incorporates the various epistemologies that have been used by theologians, philosophers, and metaphysicians, without giving undue prominence to one particular epistemology. For example, this approach links empirical and rational methods, combines deductive and inductive logic, brings together subjective and objective elements, among other things.